Sustainable Marketing Strategy Focuses on 4P for MSMEs - Mujiyanti, Sri Ayudha; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sustainable marketing has become an interesting topic as people around the world begin to realize the importance of preserving the environment. Sustainable marketing strategies focusing on the 4Ps (product, price, place, and promotion) have been applied to various businesses and enterprises. This study seeks and organizes how these strategies have been practiced in the business world so that they can be a consideration for MSMEs to identify which strategies can be chosen to be practiced according to their business conditions. This study is a qualitative literature review study from sources in the form of literature published in the last 10 years. The implementation of sustainable marketing often requires significant initial capital or investment such as the use of environmentally friendly materials, technology investment, and certification.